Turkey: Towards a Eurasian Shift? - Valeria Talbot (Pubblicazioni ISPI, 2018)
Over the last few years, Turkey seems to have embraced the East again. Ankara's closer relations with Eurasian countries go hand in hand with the global shift eastwards, towards the ever-growing and most dynamic region in the world. It is therefore the result of an increasing differentiation of Turkey's foreign relations, driven by strategic, economic and energy interests. Stronger ties with Eurasian countries, i.e. Russia and China, are also the litmus test for the ups and downs in relations with Washington and Brussels. While Ankara still retains strong ties with the West, it is laying the groundwork to further widen its interests to the East. This report aims to analyse the multi-faceted aspects of Ankara's Eurasian shift, highlighting the domestic drivers of Turkey's "Eurasianism", the interests at stake, the areas of cooperation and competition, and last but not least the implications for the EU.